Coconut Vendor, Downtown Port of Spain - (:unkn) unknown (H.O. Thomas, 2009)
A picture of a coconut vendor in Down-town Port of Spain plying his trade with a customer satisfying his thirst with the milk of the coconut. Postcard numbered C-32531.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Coconut--Trinidad and Tobago; Street vendors--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Donkeys--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain